Dinamika Husnuzzhan pada Remaja Tunadaksa Berprestasi - Rahmawati; Fadhila, Mahdia (Faculty of Ushuluddin and Humanities, 2024)
Adolescence is a phase where individuals are required to live optimally, including adolescents with physical disabilities. This qualitative case study aims to describe the dynamics of husnuzan among high-achieving adolescents with disabilities and the influencing factors. The results show that both subjects have accepted their physical limitations and are able to maintain a husnuzan attitude by continually striving to improve themselves and achieve. However, this attitude sometimes experiences cognitive and affective dynamics that affect their daily behavior. The influencing factors include religiosity, spirituality, psychology, and social support.